If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + p = 12 Solving 2m + p = 12 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1p' to each side of the equation. 2m + p + -1p = 12 + -1p Combine like terms: p + -1p = 0 2m + 0 = 12 + -1p 2m = 12 + -1p Divide each side by '2'. m = 6 + -0.5p Simplifying m = 6 + -0.5p
| 4y-14=19 | | 0.02(y-6)+0.20y=0.12y-0.3 | | 6(3s+3)=234 | | 3x-1=x^0 | | -9x^2-45x+4500=0 | | 250=x*1.5 | | (2x+40)+5x=180 | | Log(n+2)=Log(3n-2) | | 5x-4=94-9x | | 8(2l+5)=56 | | 4x+3/15=1/3 | | 175=35+10w | | y=2x^2+16x+c | | 4x+(2x+30)=360 | | 5x-4=94-x | | 5(-2r+2)+2r=5r+36 | | 4x^2-80x+200=0 | | 4x^2-80x+200=o | | -17+44=-3(x+5) | | 9x+1=5x+33 | | 4x^2-25x+34=-2x+6 | | 84/50 | | 19x-4=12x-11 | | 3/4x-1/8=1/4 | | (5n+2)=1n-3n | | 14+2=-2(3x-8) | | 14+2=-2(3-8) | | 2m=o | | -16+5x=4x(3x+7) | | 9/8y-12=-3 | | 3/5r=15 | | 9+2x=-3 |